That’s funny … you don’t look like a lecturer! dress and professional identity of female academics - Tsaousi, Christiana (My University, 2020)
This paper focuses on how female academics in UK universities use dress to construct their professional identity. The paper draws on the current literature on dress, body and academic identity and uses a theoretical framework of Goffman’s work of performance and Bourdieu’s concepts of cultural capital and habitus to explore these women’s attempts to construct themselves as professionals. The aim of this paper is to give insights into these women’s perceptions of ‘what it takes to dress to impress’ for the ‘professional project’ within a constantly shifting university workplace environment. The themes of analysis include issues such as the challenges of being a female academic and establishing yourself in the class, using dress to establish a feeling of belonging in the department and institution as a whole and a critique of how the various aspects of dress are incorporated in this idea of visual gratification of the ‘consuming’ students.
Keywords: Academic identity; Bourdieu; Dress; Female academics; Goffman; Professional identity